2005
DOI: 10.1002/dev.20082
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific differences and similarities in the behavior of hand-raised dog and wolf pups in social situations with humans

Abstract: In order to reveal early species-specific differences, we observed the behavior of dog puppies (n ¼ 11) and wolf pups (n ¼ 13) hand raised and intensively socialized in an identical way. The pups were studied in two object-preference tests at age 3, 4, and 5 weeks. After a short isolation, we observed the subjects' behavior in the presence of a pair of objects, one was always the subject's human foster parent (caregiver) and the other was varied; nursing bottle (3 weeks), unfamiliar adult dog (3 and 5 weeks), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 35 publications
(38 reference statements)
1
122
1
1
Order By: Relevance
“…As an analogy one could assume that the domestication process of dogs had to aVect their ability to communicate with humans. Previous results have shown that, compared to wolves raised identically, dogs have an increased tendency to have eye contact with humans in various situations (Miklósi et al 2003;Gácsi et al 2005). Since in human communication the dynamics of eye-contact plays a crucial role (Carpenter et al 1995;Gomez 1996;Tomasello 1995;Trevarthen 1979) also dogs in human groups might have gained an advantage if they had acquired the ability to use this communicative skill Xexibly (Miklósi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an analogy one could assume that the domestication process of dogs had to aVect their ability to communicate with humans. Previous results have shown that, compared to wolves raised identically, dogs have an increased tendency to have eye contact with humans in various situations (Miklósi et al 2003;Gácsi et al 2005). Since in human communication the dynamics of eye-contact plays a crucial role (Carpenter et al 1995;Gomez 1996;Tomasello 1995;Trevarthen 1979) also dogs in human groups might have gained an advantage if they had acquired the ability to use this communicative skill Xexibly (Miklósi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There were many regular and occasional visitors at the wolf farm most of whom made short contacts with the wolves. As a result of this socialisation regime, the wolves displayed no sign of wariness or avoidance in the presence of humans (even strangers), in contrast, they were keen to interact with unfamiliar persons Gácsi et al 2005;Virányi et al 2002). They also showed no fear of the testing apparatus at any time and adapted very skilfully to the rules of the testing situation.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed large differences between species in recognising the focus of human attention, with dogs (Canis lupus familiaris) out-performing other species, including chimpanzees Hare et al 2002). The partially contradictory studies by Hostetter et al 2007, Gácsi et al 2005, Theall and Povinelli 1999, and Virányi et al 2004 provoked lively discussion over whether the studies should be assessed on a behavioural or a cognitive representational level. While behavioural explanations (Povinelli and Vonk 2003) emphasise the animal's ability to learn to use the focus of attention as a cue, cognitive explanations highlight the animal's understanding of the signaller's intentions .…”
Section: Introductionmentioning
confidence: 99%
“…We used point-light display of a human figure as stimulus because humans are highly relevant 89 social partners for dogs (Nitzschner et al, 2012) to an extent that in some contexts they prefer humans over 90 conspecifics both at the behavioural (Gácsi et al, 2005) and at the neural (Andics et al, 2014) levels. We also 91 aimed to study the physiological consequences of intranasal oxytocin administration (changes in heart rate and 92 heart rate variability) and how the individuals' physiological reaction to oxytocin correlates with the looking 93 preferences in dogs.…”
mentioning
confidence: 99%